Transferable skills perception analysus of vocational teachers on-in-on-in dual skills program - Purnomo Purnomo; Marsono Marsono; Tuwoso Tuwoso (Jurnal Pendidikan Vokasi, 2021)
The Ministry of Education and Culture in 2016 made one of the breakthrough programs in an effort to organize and fulfill productive teachers in Vocational High Schools (VHS), namely through the Dual Skills Program (DSK). The DSK is implemented to support the improvement of vocational education as well as education and job skills training. Meanwhile, DSK participating teachers must have new competencies that can be used to teach productive subjects in certain areas of expertise. Increasing the competence of DSK participants needs to take into account the development of transferable skills obtained after conducting training or in the process of implementing DSK. The aims of this study are to 1.) Determine the types of transferable skills that DSK participant teachers need to possess; and 2.) Analyze and describe the transferable skills of teachers of vocational high school on-in-on-in DSK in Malang Regency. This study uses a quantitative approach. The samples used were all vocational high school teachers who took part in the on-in-on-in DSK in Malang Regency, while the respondent's data collection used a questionnaire. The results showed that the types of transferable skills consist of communication skills, planning skills, interpersonal skills, work attitude skills, organizational skills, financial management skills, and critical thinking skills. The transferable skills of teachers of vocational high school on-in-on-in DSK in Malang Regency were in a good category.